2022
DOI: 10.1021/acs.nanolett.1c04354
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Wrinkle-Structured Catalyst Layer/Membrane Interface for Ultralow Pt-Loading Polymer Electrolyte Membrane Fuel Cells (PEMFCs)

Abstract: The optimal architecture of three-dimensional (3D) interface between a polymer electrolyte membrane (PEM) and catalyst layer (CL) is one of the most important issues to improve PEM fuel cells' (PEMFCs) performance. Here, we report the fabrication of hierarchical wrinkled PEM/CL interface over a large area. We fabricated the hierarchical wrinkles on a multiscale from nanometers to micrometers by bottom-up-based facile, scalable, and simple method. Notably, it allows one to go beyond the limit of the catalyst ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…In similar work with the use of a multiscale patterned mold, recently, Lee et al. [ 92 ] reported a method for making hierarchical wrinkles patterned polymeric mold consisting of three different pattern sizes of 0.4, 3, and 10 µm by using repetitive heat‐induced mechanical deformation between a stiff top skin layer and a soft bottom. The constructed pattern was replicated by PDMS mold like the previously introduced study.…”
Section: Surface Modification Of Membranementioning
confidence: 99%
See 1 more Smart Citation
“…In similar work with the use of a multiscale patterned mold, recently, Lee et al. [ 92 ] reported a method for making hierarchical wrinkles patterned polymeric mold consisting of three different pattern sizes of 0.4, 3, and 10 µm by using repetitive heat‐induced mechanical deformation between a stiff top skin layer and a soft bottom. The constructed pattern was replicated by PDMS mold like the previously introduced study.…”
Section: Surface Modification Of Membranementioning
confidence: 99%
“…Compared with the MEA with a flat membrane, it exhibited an increment of ≈40%; its performance was also higher than that of each single-scale pattern used for constructing multiscale structures (Figure 5c). In similar work with the use of a multiscale patterned mold, recently, Lee et al [92] reported a method for making hierarchical wrinkles patterned polymeric mold consisting of three different pattern sizes of 0.4, 3, and 10 µm by using repetitive heat-induced mechanical deformation between a stiff top skin layer and a soft bottom. The constructed pattern was replicated by PDMS mold like the previously introduced study.…”
Section: Multiscale Patterned Membranesmentioning
confidence: 99%
“…Lee et al [ 66 ] presented the fabrication of an interface composed of a polymer electrolyte membrane (PEM) and a hierarchically wrinkled catalyst (CL) layer (PEM/CL) in a PEM fuel cell (PEMFC) by bottom-up methods ( Figure 15 ). Heat-induced repetitive mechanical deformations between a rigid top skin and a soft bottom substrate were used to fabricate these wrinkles.…”
Section: Desing Of Adaptive Wrinkled Patterned Surfaces: Reversible S...mentioning
confidence: 99%
“…( b ) Fabrication of hierarchical wrinkles through repetitive heat-induced wrinkling processes and ( c ) Transfer of wrinkled hierarchical structures to Nafion membrane by thermal lamination and subsequent CL coating. Reproduced permission from with reference [ 66 ]. Copyright 2022, American Chemical Society (ACS).…”
Section: Figurementioning
confidence: 99%
“…g) Schematic illustration of catalyst layer/membrane interface using wrinkle-based hierarchical structure for ultralow Pt-loading polymer electrolyte membrane fuel cells. Reproduced with permission [28]. Copyright 2022, American Chemical Society.…”
mentioning
confidence: 99%